Optical synchronous signal demodulation-based quartz-enhanced photoacoustic spectroscopy for remote, multi-point methane detection in complex environments - Bo Sun; Tingting Wei; Mingjiang Zhang; Lijun Qiao; Zhe Ma; Angelo Sampaolo; Pietro Patimisco; Vincenzo Spagnolo; Hongpeng Wu; Lei Dong (Photoacoustics)
We present a novel optical synchronized signal demodulation (OSSD) method applied in quartz-enhanced photoacoustic spectroscopy (QEPAS) for remote gas sensing. Using 1 % of the laser source as an optical synchronization signal, kilometer-scale remote gas detection was achieved, overcoming the challenges of long-distance real-time detection in complex environments with conventional QEPAS. A time-sharing OSSD-QEPAS system for sewer methane detection was subsequently developed. The system’s modulation depth was optimized, and the catalytic effect of water vapor on photoacoustic signals was validated, resulting in a CH₄ sensor achieving a detection limit of 445 ppb with a 300-ms averaging time, and an excellent linear dynamic range with a R2 = 0.999. To demonstrate the stability, robustness, and accuracy of the OSSD-QEPAS system, continuous methane measurements covering a 14-hour period at two different sewer locations on campus were performed.